Pilot longitudinal mosquito surveillance study in the Danube Delta Biosphere Reserve and the first reports of Anopheles algeriensis Theobald, 1903 and Aedes hungaricus Mihályi, 1955 for Romania - Török, Edina; Tomazatos, Alexandru; Cadar, Daniel; Horváth, Cintia; Keresztes, Lujza; Jansen, Stephanie; Becker, Norbert; Kaiser, Achim; Popescu, Octavian; Schmidt-Chanasit, Jonas; Jöst, Hanna; Lühken, Renke (Parasites & vectors, 2016)
Mosquito-borne viruses (moboviruses) are of growing importance in many countries of Europe. In Romania and especially in the Danube Delta Biosphere Reserve (DDBR), mosquito and mobovirus surveillance are not performed on a regular basis. However, this type of study is crucially needed to evaluate the risk of pathogen transmission, to understand the ecology of emerging moboviruses, or to plan vector control programmes.
Gesehen am 27.05.2020